2014
DOI: 10.1186/1746-4358-9-15
|View full text |Cite
|
Sign up to set email alerts
|

Process-oriented training in breastfeeding for health professionals decreases women’s experiences of breastfeeding challenges

Abstract: BackgroundThe World Health Organization recommends promoting exclusive breastfeeding for six months. Women often end breastfeeding earlier than planned, however women who continue to breastfeed despite problems often experience good support and counselling from health professionals. The aim of this study was to evaluate the effects of a process-oriented training in breastfeeding support counselling for midwives and child health nurses, on women’s satisfaction with breastfeeding counselling, problems with insuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(71 citation statements)
references
References 39 publications
0
68
0
3
Order By: Relevance
“…Previous studies that have found individual, on-going face-to-face support [ 36 ] consisting of relationship-building [ 37 ] and characterized by authentic presence [ 56 ] is key for breastfeeding continuation. In addition, a process-oriented training in breastfeeding for health care professionals influenced women’s abilities to handle breastfeeding difficulties [ 57 ]. It is thus obvious that support is important in order to promote further breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that have found individual, on-going face-to-face support [ 36 ] consisting of relationship-building [ 37 ] and characterized by authentic presence [ 56 ] is key for breastfeeding continuation. In addition, a process-oriented training in breastfeeding for health care professionals influenced women’s abilities to handle breastfeeding difficulties [ 57 ]. It is thus obvious that support is important in order to promote further breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy [12], the perception of milk supply [9,13-17], and initiation and strength of intention to breastfeed [18-20] are reported as modifiable breastfeeding determinants. Self-efficacy, for example, is associated with the perception of being supported [9], exposure to breastfeeding activities [9], early breastfeeding practice [5], and past experience [9].…”
Section: Introductionmentioning
confidence: 99%
“…Self-efficacy, for example, is associated with the perception of being supported [9], exposure to breastfeeding activities [9], early breastfeeding practice [5], and past experience [9]. Perception of milk supply, on the other hand, depends on mothers’ self-efficacy and level of knowledge and skills [12]. Sufficient breastfeeding knowledge and skills may help mothers avoid physical discomfort [21].…”
Section: Introductionmentioning
confidence: 99%
“…U žen kojících přes tři měsíce nebyly prokázány významné rozdíly mezi ženami z intervenční a kontrolní skupiny. Tento program pro zdravotníky k podpoře schopností žen řešit problémy s kojením, se prokázal jako účelný u žen výlučně kojících do třech měsíců (11).…”
Section: Rozvoj Edukačních Dovedností Zdravotníkůunclassified